1996
DOI: 10.1038/bjc.1996.402
|View full text |Cite
|
Sign up to set email alerts
|

Screening for prostate cancer using serum prostate-specific antigen: a randomised, population-based pilot study in Finland

Abstract: Summary The possibility of screening the general population for prostate cancer using serum prostate-specific antigen (PSA) level (alone or in combination with other tests) as screening test has recently been discussed. A number of studies are on the way, but the published reports have almost exclusively been based on men volunteering for screening. We assessed the feasibility of a screening study based on men identified from a central population registry. A random sample of 600 men in the age groups 55, 60 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Screening and early detection thus can identify many of the silent tumors (stage A1, usually asymptomatic) in the population. Screening program in western countries detect prostate cancer in 2.0-4.8% of those screened [9][10][11][12][13][14][15][16][17][18], but the rate is only 1.1-1.3% in Japanese men [19][20][21]. We found that PSA increased the detection rate of early stage of prostate cancer.…”
Section: Discussionmentioning
confidence: 86%
“…Screening and early detection thus can identify many of the silent tumors (stage A1, usually asymptomatic) in the population. Screening program in western countries detect prostate cancer in 2.0-4.8% of those screened [9][10][11][12][13][14][15][16][17][18], but the rate is only 1.1-1.3% in Japanese men [19][20][21]. We found that PSA increased the detection rate of early stage of prostate cancer.…”
Section: Discussionmentioning
confidence: 86%
“…Finland became the third partner to enter the ERSPC [7]. A summary of the first three pilot studies is presented in Table 1[8–10].…”
Section: Results Of Pilot Studiesmentioning
confidence: 99%
“…Grant applications were successful in Belgium and the Netherlands, and the European Union was ready to continue financing the international co‐ordination. The ERSPC started on 1 July 1994, and Finland joined a year later after successfully conducting a pilot study [7].…”
Section: Structuring the Erspcmentioning
confidence: 99%
“…Although most prostate tumors are slow growing and do not cause serious mortality, some are fast growing and may metastasize rapidly and widely to other organs especially to the bone. The silen 'latent' cancers that are unlikely to progress to cause significant mor bidity and mortality are found at autopsy or incidentally and represent 80% of the early prostate cancers, whereas the other 20% are 'clinical' cancers that are likely to progress to cause disease and are potentially lethal and life-threatening [32][33][34], Thirty percent of men older than 50 years of age harbor one form or the other, i.e., 6% prevalence rate of 'clinical' cancer [32], As shown in table 3, PSA-based screening tests have been performed during the past sev eral years in various regions of the world [23,24,[31][32][33][34][35][36][37][38][39][40][41], Prostate cancer detection rates range from 1 % in Japan to 4.8% in the US and appear to be proportional to incidence rate in these countries. Of interest to note are the findings of the trials where both clinical and pathological stagings are detailed [23,33,34,36,39].…”
Section: Psa In Screening and Early Detection Of Prostate Cancermentioning
confidence: 99%